Analisis tahapan asesmen diagnostik kognitif dalam pembelajaran bahasa Indonesia di sekolah dasar - Wahyuni, Tri; Matsuri, Matsuri; Ardiansyah, Roy (Universitas Sebelas Maret, 2025)
The aim of this research is to describe how teachers implement the phases of cognitive diagnostic evaluation in Indonesian learning. Qualitative research method with a descriptive approach. The research's participants include school administrators, teachers, and students. Data collecting strategies include interviews, observations, and documentation. The Miles and Huberman model is used while analysing data. The execution of diagnostic assessment at SDN Gedangan 2 is examined based on diagnostic assessment stages that have successfully completed the planning, implementation, and follow-up/diagnosis stages